The Image of Muhammad in the Christian Version of the Legend of Sergius Bahira on the Example of a Long Arab Review (Phantom of Muhammad, Shade of Samuel Byzantine Empire in Relation to Members of Other Cultures and Religions (7th–15th c.): No. XXXIX, 2020)
The image of Muhammad which emerges from Bahira’s Christian legend is far from being objective, but it allows to learn what people in Byzantium and in Europe knew about Islam and how they attempted to explain the convergence of its doctrine with Christianity. For Christian authors, it was also the opportunity to bring the founder of Islam closer to the readers.